XV International Conference on Durability of Building Materials and Components. eBook of Proceedings 2020
DOI: 10.23967/dbmc.2020.024
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength Improvement and Water Permeability of Self-Healing Concrete Using Bacillus Subtilis Natto

Abstract: In recent years, many projects have been carried out to enhance the durability of concrete structure from the influence of cracks. Generally, managing cracks should be a rather preventative method for sustainable development. Based on that, Bacillus subtilis natto-a local bacterium in Japan was found to have the ability to form CaCO 3 , which can be used as healing materials for cracks in the concrete structure. The bacterial biomineralization immobilized in lightweight aggregate was studied to improve the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…A wide range of bacteria [38], including Sporosarcina pasteurii [2,[46][47][48][49][50][51][52][53][54][55], Bacillus Subtilis [14,[16][17][18]40,[56][57][58][59], Bacillus Cereus [20,60,61], and Bacillus Megaterium [23,24,62,63], as well as enzymes isolated from plants, such as Jack bean [42,45,64] and soybean [36,41,44], have been investigated in the literature. Navigating through the literature, however, it can be observed that Sporosarcina pasteurii (S. pasteurii) is the most widely employed bacteria, as it demonstrates a higher rate and quality of calcium carbonate precipitation due to its species characteristics [65,66].…”
Section: Bio-cementing Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of bacteria [38], including Sporosarcina pasteurii [2,[46][47][48][49][50][51][52][53][54][55], Bacillus Subtilis [14,[16][17][18]40,[56][57][58][59], Bacillus Cereus [20,60,61], and Bacillus Megaterium [23,24,62,63], as well as enzymes isolated from plants, such as Jack bean [42,45,64] and soybean [36,41,44], have been investigated in the literature. Navigating through the literature, however, it can be observed that Sporosarcina pasteurii (S. pasteurii) is the most widely employed bacteria, as it demonstrates a higher rate and quality of calcium carbonate precipitation due to its species characteristics [65,66].…”
Section: Bio-cementing Agentsmentioning
confidence: 99%
“…Calcium carbonate (CaCO 3 ) precipitation is a naturally occurring phenomenon in different environments, including marine water, freshwater, and soils. Microbially induced calcium carbonate precipitation Induced Calcium Carbonate Precipitation (MICP), which exploits the microbial metabolic processes for bio-cementation to enhance the durability of construction materials, has drawn attention not only in soil stabilization [1][2][3][4][5][6][7][8][9][10][11] and building construction [12][13][14][15][16][17][18][19][20][21][22] but also in wind-induced desertification [23][24][25][26], stone artwork conservation [27], and even subsurface-related applications [28,29]. Microorganisms engaged in the nitrogen cycle, sulphate-reducing bacteria, and photosynthetic microorganisms have all been reported to induce calcium carbonate [30,31].…”
Section: Introductionmentioning
confidence: 99%